Diagnostic value of dynamic contrast-enhanced magnetic resonance imaging in Bell's palsy. (September 2021) - Wang, Ying; Tang, Weiqing; Chai, Yongchuan; Zhu, Weidong; Li, Xiaoyan; Wang, Zhaoyan
Background: Bell's palsy (BP) is the most common form of acute facial nerve disorder and is characterized by rapid onset peripheral facial palsy of unknown etiology. Purpose: To explore the diagnostic value of dynamic contrast-enhanced (DCE) magnetic resonance imagine (MRI) in patients with BP particularly in involved segments. Material and Methods: A retrospective analysis was performed on the patients with BP who underwent routine MRI examinations and volumetric interpolated breath-hold examination (VIBE) sequence-based DCE-MRI before surgery in our department from January 2015 to July 2020. DCE-MRI data postprocessing was performed on Siemens Workstation Extended MR Work Space 2.6.3.5. Statistical analyses were performed using SPSS®v.19.0. The inter-observer reliability was evaluated with kappa identity test and McNemar's test. Results: Twenty-three patients were included. On conventional contrast-enhanced MRI, the two observers were inconsistent in their diagnosis of lesion segments of facial nerve (Kappa 0.426, P  = 0.009). Compared to the results of the surgery, the diagnostic consistency of both observers was general (Kappa 0.476, P  < 0.001 and Kappa 0.430, P  < 0.001, respectively). The diagnostic results of DCE-MRI for lesion segments of the facial nerve were consistent between the two observers (Kappa 0.929, P  < 0.001). Compared to the results of the surgery, the diagnostic consistency of both observers was good (Kappa 0.753, P  < 0.001 and Kappa 0.731, P  < 0.001, respectively). Conclusion: Compared to conventional MRI, DCE-MRI has good stability and repeatability in the diagnosis of the lesion segments of the facial nerve as well as a good specificity and accuracy.